2019
DOI: 10.1111/imcb.12297
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia aggravates acute liver injury by promoting liver‐resident macrophage NLRP3 inflammasome activation via the inhibition of AMPK/mTOR‐mediated autophagy induction

Abstract: Although the detrimental effects of diabetes mellitus/hyperglycemia have been observed in many liver disease models, the function and mechanism of hyperglycemia regulating liver-resident macrophages, Kupffer cells (KCs), in thioacetamide (TAA)-induced liver injury remain largely unknown. In this study, we evaluated the role of hyperglycemia in regulating NOD-like receptor family pyrin domain-containing 3 protein (NLRP3) inflammasome activation by inhibiting autophagy induction in KCs in the TAA-induced liver i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Accordingly, we noted that doxepin treatment led to increases in serum CRP, IL-1β, and TNF-α levels in our doxepin-treated mice, in parallel with glucose intolerance exacerbation ( Figure S7 ). Alternatively, hyperglycemia contributed to Kupffer cells activating and then secreting proinflammatory cytokines such as TNF-α and IL-6 [ 67 , 68 ]. Higher TNF-α levels lead to liver injury mediated by hepatocellular apoptosis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we noted that doxepin treatment led to increases in serum CRP, IL-1β, and TNF-α levels in our doxepin-treated mice, in parallel with glucose intolerance exacerbation ( Figure S7 ). Alternatively, hyperglycemia contributed to Kupffer cells activating and then secreting proinflammatory cytokines such as TNF-α and IL-6 [ 67 , 68 ]. Higher TNF-α levels lead to liver injury mediated by hepatocellular apoptosis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasomes are multiprotein complexes that sense danger signals like DAMPs and pathogen-associated molecular patterns (PAMPs) from damaged cells and pathogens (79). There are multiple inflammasomes implicated in liver disorders, but the nucleotide-binding oligomerization domain (NOD)-like receptor protein 3 (NLRP3) inflammasome has been studied most extensively (80)(81)(82). The NLRP3 inflammasome is activated in a two-step process.…”
Section: The Nlrp3 Inflammasome Caspase-1 Pathwaymentioning
confidence: 99%
“…Studies have found that DM could be considered as a risk factor for nonalcoholic fatty liver disease [ 3 ]. In addition, hyperglycemia was reported to exaggerate acute liver injury through inflammasome activation [ 4 ]. The deficiency of intracellular glucose in hepatic cells during DM results in damaging and necrotic effects, which stimulate apoptotic response [ 5 ].…”
Section: Introductionmentioning
confidence: 99%